2019
DOI: 10.1007/s00018-019-03346-4
|View full text |Cite
|
Sign up to set email alerts
|

Human erythrocytes: cytoskeleton and its origin

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature Switzerland AG. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 127 publications
3
32
0
Order By: Relevance
“…Accordingly, their derivatization with thiol reagents are reported to block ankyrin interaction and a specific antibody raised against a synthetic peptide containing Cys-201 acts as a potent inhibitor of ankyrin binding [ 55 ]. Moreover, band 4.1 and 4.2 proteins, key components of the cytoskeleton network [ 56 ], also contain accessible cysteines [ 57 , 58 ]. In conclusion, a large body of literature, accumulated over several years by our group and others, clearly demonstrates the RBC structural and metabolic alterations induced by Hg, indicating severe alterations in the physiology and morphology of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, their derivatization with thiol reagents are reported to block ankyrin interaction and a specific antibody raised against a synthetic peptide containing Cys-201 acts as a potent inhibitor of ankyrin binding [ 55 ]. Moreover, band 4.1 and 4.2 proteins, key components of the cytoskeleton network [ 56 ], also contain accessible cysteines [ 57 , 58 ]. In conclusion, a large body of literature, accumulated over several years by our group and others, clearly demonstrates the RBC structural and metabolic alterations induced by Hg, indicating severe alterations in the physiology and morphology of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that blood cells grow in suspension, and the process of erythropoiesis is accompanied by great changes in cell morphology. The cell size gradually increases as hematopoietic progenitor cells (HPCs) differentiate into precursors (7), and then decreases during erythroblast maturation accompanied by cytoskeleton remodeling and loss of cytoplasmicnuclear connections (7,8). Moreover, some studies have revealed that the self-renewal and differentiation of HSCs are affected by cell morphology and adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized tissue processing and fixation requirements for microtubule visualization precluded confirmatory studies on patient marrow samples. However, prior studies have shown that freshly obtained human peripheral red blood cells (RBC) retain remnant microtubule fragments that are disrupted by the microtubule destabilizer nocodazole [30][31][32][33] . IF for β-tubulin on RBC from non-anemic control patients confirmed the previously described pancellular stippling in the majority (>80%) of cells.…”
Section: Resultsmentioning
confidence: 99%